2001
DOI: 10.4049/jimmunol.166.4.2801
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A (apoSAA) Expression Is Up-Regulated in Rheumatoid Arthritis and Induces Transcription of Matrix Metalloproteinases

Abstract: The acute-phase reactant rabbit serum amyloid A 3 (SAA3) was identified as the major difference product in Ag-induced arthritis in the rabbit, a model resembling in many aspects the clinical characteristics of rheumatoid arthritis (RA) in humans. In Ag-induced arthritis, up-regulated SAA3 transcription in vivo was detected in cells infiltrating into the inflamed joint, in the area where pannus formation starts and, most notably, also in chondrocytes. The proinflammatory cytokine IL-1β induced SAA3 transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
0
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 34 publications
9
118
0
4
Order By: Relevance
“…Additionally, Migita et al (51) found that degradation of SAA is impaired in monocytes stimulated by IL-1␤ and interferon-␥. In turn, SAA induces the secretion of both MMP-1 and MMP-3 by synoviocytes and chondrocytes (52) and stimulates MMP-9 up-regulation in monocytes. Moreover, several studies have recently focused on the physiologic role of acute-phase SAA as a potent chemoattractant of neutrophils, T cells, and monocytes, the latter through CCL2 production via formyl peptide receptor-like 1 (53).…”
Section: Future Directions In the Study Of A Highly Complex Diseasementioning
confidence: 98%
“…Additionally, Migita et al (51) found that degradation of SAA is impaired in monocytes stimulated by IL-1␤ and interferon-␥. In turn, SAA induces the secretion of both MMP-1 and MMP-3 by synoviocytes and chondrocytes (52) and stimulates MMP-9 up-regulation in monocytes. Moreover, several studies have recently focused on the physiologic role of acute-phase SAA as a potent chemoattractant of neutrophils, T cells, and monocytes, the latter through CCL2 production via formyl peptide receptor-like 1 (53).…”
Section: Future Directions In the Study Of A Highly Complex Diseasementioning
confidence: 98%
“…30 SAA3 was shown to induce several species of MMPs in chondrocytes. 31 Whichever event comes first, vascular destabilization, if any, or upregulation of endogenous TLR4 agonists may serve as a danger signal even before the eventual arrival of the true danger, metastasizing tumor cells. Injection of LLC or 3LL, a highly metastatic variant of LLC, into the tail vein of mice to block pulmonary homing and spontaneous metastasis by inhibition of the S100A8-SAA3-TLR4 system, respectively, demonstrates that the fourth and fifth steps in metastasis and, as a consequence, the final regrowth step, are regulated by TLR4.…”
Section: Acquisition Of Metastatic Potential In Primary Tumorsmentioning
confidence: 99%
“…SAA, like CRP, is thought to play a role in innate defense by binding Gram-negative bacteria and acting as an opsonin (2). SAA is also expressed in apparently normal tissues, particularly the epithelium, and is deposited in numerous inflammatory tissues and implicated in the pathogenesis of infection, trauma, neoplasia, rheumatoid synovitis, atherosclerosis, and Alzheimer's disease (3)(4)(5)(6). It has a multifunctional role in the pathogenesis of amyloidosis and is thought to contribute to this potentially fatal consequence of chronic inflammation (7).…”
Section: Serum Amyloid a Induces Monocyte Tissue Factormentioning
confidence: 99%